Impact of Feedback on the Performance of University Students - Villoro Armengol, Jordi; Hinojosa Alcalde, Ingrid; González Ibáñez, Daniel; Estaún Ferrer, Santiago (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This study aims to provide data to determine the extent to which feedback influences academic performance. An experiment was conducted with university students in the marketing and physical education programs. The exhibit was divided into three groups based on the type of information -feedback- that was provided to them. The results show that there is a link between the information provided and the results obtained. When the information is correct, the performance improves accordingly. These findings have served to reinforce the teacher's commitment to provide feedback with responsibility and academic rigor.